Mean Change in Respiratory Functions With Paracentesis in Chronic Hepatitis C Patients With Cirrhotic Ascites - Mukhtar, Faizah; Ahmed, Moazama Shakeel (Biological and Clinical Sciences Research Journal, 2025)
Chronic Hepatitis C (CHC) with cirrhotic ascites is associated with significant respiratory dysfunction due to mechanical compression of the diaphragm and lungs. Objective: To evaluate the mean change in respiratory functions following paracentesis in patients with chronic Hepatitis C and cirrhotic ascites. Methods: A cross-sectional study was conducted at the Department of Internal Medicine, Akhtar Saeed Trust Hospital, Lahore. A total of 154 patients aged 25-65 years with chronic Hepatitis C and cirrhotic ascites were enrolled. Patients underwent baseline assessments of respiratory function, including circumferential measurements and ventilometry, 30 minutes before and after paracentesis. Results: Significant improvements in respiratory function were observed following paracentesis. Tidal volume increased by 90 ± 50 mL (p < 0.001), minute volume by 0.8 ± 0.4 L/min (p < 0.001), and vital capacity by 0.6 ± 0.3 L (p < 0.001). Respiratory rate decreased by 2 ± 1 breaths/min (p < 0.001). Circumferential measurements at axillary, xiphoid, and umbilical reference points showed significant reductions, indicating decreased abdominal pressure. These improvements were consistent across gender and age groups. Conclusion: Paracentesis significantly improves respiratory function in patients with chronic Hepatitis C and cirrhotic ascites. The procedure reduces intra-abdominal pressure, enhances lung expansion, and improves ventilatory parameters. Paracentesis should be considered a valuable therapeutic intervention for both ascites and respiratory dysfunction in this patient population.